Evaluation of iron-containing carbon nanotubes by near edge X-ray absorption technique. (October 2015) - Osorio, A.G.; Bergmann, C.P.
Abstract: The synthesis of carbon nanotubes (CNTs) via Chemical Vapor Deposition method with ferrocene results in CNTs filled with Fe-containing nanoparticles. The present work proposes a novel route to characterize the Fe phases in CNTs inherent to the synthesis process. CNTs were synthesized and, afterwards, the CNTs were heat treated at 1000 °C for 20 min in an inert atmosphere during a thermogravimetric experiment. X-Ray Absorption Spectroscopy (XAS) experiments were performed on the CNTs before and after the heat treatment and, also, during the heat treatment, e.g., in situ tests were performed while several Near-Edge X-Ray Absorption (XANES) spectra were collected during the heating of the samples. The XAS technique was successfully applied to evaluate the phases encapsulated by CNTs. Phase transformations of the Fe-based nanoparticles were also observed from iron carbide to metallic iron when the in situ experiments were performed. Results also indicated that the applied synthesis method guarantees that Fe phases are not oxidize. In addition, the results show that heat treatment under inert atmosphere can control which phase remains encapsulated by the CNTs. Highlights: CNTs filled with Fe-based nanoparticles were heat treated in inert atmosphere. EXAFS analysis was performed on CNTs, and LCF and FT were obtained. In situ XANES measurements were performed during the heating of the samples. Fe-based particles change from Fe carbide to metallic Fe during the heat treatment. The applied synthesis method guarantees that Fe phases are not oxidize.